KARAKTERISTIK EDIBLE FILM BERBAHAN BAKU PATI UBI TALAS DENGAN PENAMBAHAN LILIN LEBAH (BEESWAX) - Devinta Puspita Sari; Farida Hanum Hamzah; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The purpose of this study to obtain the best characteristics of edible film from different concentration of beeswax. This research was carried out experimentally with five treatments and three replications to obtain 15 experimental units. The treatments in this study research were concentration of beeswax such as LB1 (0.1% beeswax), LB2 (0.2% beeswax), LB3(0.3% beeswax), LB4 (0.4% beeswax), and LB5 (0, 5% beeswax). The parameters observed are thickness, solubility, water vapor transfer rate test, tensile strength and edible film elongation. The selected treatment based on the parameters tested was LB5 treatment with the use of beeswax concentration of 0.5%. Edible film LB5 treatment has a thickness value of 0.17 mm, a solubility of 22.27%, a water vapor transfer rate test of 15.88 g/m2/h, tensile strength of 0.37 MPa and elongation of 9,29%.Keywords:beeswax, edible film